Proposta para a gestão do território do Geoparque Aspirante Quarta Colônia/RS, com base na análise do seu capital social - Ziemann, Djulia Regina (2020)
This paper aims to discuss the proposal of institutional arrangements and territorial management measures for better use of the geotouristic potential of the Aspirant Geopark Quarta Colonia. It also analyzes the network actions between the social actors with activities related to tourism present in the territory. The feasibility of different institutional arrangements used in consolidated geoparks and thus explaining the guidelines for strengthening the social capital present in the Quarta Colonia. The research is guided by qualitative and quantitative research and as instruments, bibliographic research, fieldwork, structured highlights, and documentary research were used. The results indicate that the territory is constituted by several social actors, responsible for strategies with great potential for development, however, the actors behave in a disconnected way and consequently, their initiatives are presented in an isolated way. Still, it is noteworthy that institutions such as UFSM and CONDESUS have been carrying out actions to organize the application of the territory as a UNESCO geopark. Concerning the analysis of management applied by the global network geoparks, considerably varied forms are observed in the management processes. Most associations are composed of a public entity, with a partnership between public and private associations. Given the reflections on the territory, its characteristics, and possible management strategies, it is understood that the best management strategy for the Aspirant Geopark Quarta Colonia is through a participatory management model. In this way, social empowerment is sought, and so it focuses on actions for greater articulation and integration of the networks of actors present in the territory and partnership with UFSM and CONDESUS. Yet, the need for more integration among institutional actors with the territory is emphasized, for better understanding of the potential and thus for planning aimed at the development of geotourism in the territory, with investments in infrastructure, dissemination, and conservation strategy in general.